Audible (Art): The invisible connections - Gomes, José Alberto (2021)
This is an introduction to a special edition of JSTA dedicated to the myriad forms of sonic connections and audible expressions. We approach three dimensions of sound in an artistic context: auditory specificities, performance dimensions, and computational listening. Sound is a complex phenomenon present in everyday life and dwelling between conscious and unconscious processes. A universe contained within itself, where every sound event has the potential to be considered aesthetic material, contributing to the proliferation of creative approaches. These specific conditions have potentiated an outbreak of sonic art genres and expressions. Listening as an epistemic process has been subjected to successive changes pushed by computation and the breeding of computational media. This essay points to visions and approaches to sound as a specific field of knowledge that can arise from, lead to, or be used as a tool of world-building.